Assessing the outcome of reintroduction efforts: Trends in population size and drivers of breeding success in alpine bearded vultures - D. Santos‐Cottin; B. Arroyo; F. Loercher; A. Brambilla; J. Terraube (Conservation Science and Practice)
Abstract Vulture populations have dramatically declined worldwide over the past few decades. In Europe, various programs have been implemented to reintroduce or restock these birds. In the Alps, the Bearded Vulture (Gypaetus barbatus) was eradicated in the early 20th century, prompting the launch of an international reintroduction program in 1986. Through intensive monitoring of Bearded Vulture breeding territories over 26 years (1995–2021), we observed spatial and temporal changes in population size and assessed environmental and individual factors influencing breeding performance across four countries in the Alpine arc. The number of breeding pairs increased steadily from 1 in 1995 to 65 in 2021, and the number of fledglings from 0 in 1995 to 42 in 2021, although we observed significant differences across areas, with slower growth in the Eastern Alps. The breeding success (proportion of clutches leading to a fledgling) of the entire Alpine population was 68%, higher than that of other European populations. Our analysis, which included individual and environmental variables, revealed that nest elevation positively influenced breeding success, while the proportion of open habitat in the territory had a negative effect. Additionally, breeding success significantly increased with the coverage of not strictly protected areas around the nest. In terms of individual factors, longer pair bonds positively affected breeding success, and pairs composed of wild‐hatched individuals had higher breeding success compared to those including released individuals. Our results confirm the overall positive trend of the reintroduced Alpine population but also highlight the increased vulnerability of the population breeding in the Eastern Alps. Additionally, our findings suggest that an effective network of protected areas can support the establishment of reintroduced populations. We also identified directions for further research to better understand the drivers of Bearded Vulture breeding success in the Alps.